Effects of Different Processing Methods on The Active Ingredients of Interior Warming Medicines - Xu, Qiaochu (International Journal of Public Health and Medical Research, 2024)
Processing drugs of traditional Chinese medicine is a kind of processing of Chinese herbal medicines, which can assist in adjusting the medicinal properties, reducing the toxicity of medicines, purifying the medicinal herbs, and increasing the therapeutic efficacy. In recent years, in addition to the process of processing itself and the clinical efficacy of the artillery products, there have been a considerable number of studies focusing on the effects of the active ingredients of Chinese medicines before and after concocting. In this paper, we summarize the relevant literature on the effects of Chinese medicine processing on the active ingredients of Chinese medicines in recent years, and explore the effects of different processing methods on the active ingredients of Interior warming herbs under the traditional classification of Chinese medicines, with the intention of providing certain reference value for the field of Chinese medicine processing.